ANTIDIABETIC ACTIVITY OF THE ETHANOLIC EXTRACT OF HEARTWOOD OF BIJASAR (PTEROCARPUS MARSUPIUM ROXB.) IN STREPTOZOTOCIN-NICOTINAMIDE INDUCED TYPE 2 DIABETIC RATS - Patil, U. K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The antidiabetic potential of the ethanolic extract of bijasar (Pterocarpus marsupium Roxb.) heartwood was evaluated in the streptozotocin-nicotinamide induced type 2 diabetic models. Graded doses of the ethanolic heartwood extract were administered to normal and experimental diabetic rats for 12 days. Significant (p < 0.05) reduction in fasting blood glucose levels were observed in the normal as well as in the treated diabetic animals. Serum insulin levels were not stimulated in the animals treated with the extract. STZ-nicotinamide induced diabetic rats administered with the extract (100 mg/kg) showed 30 and 42.2% decline in the blood glucose levels whilst a decline of 31.5 and 51.3% were observed in animals treated with 200 mg/kg of the alcoholic extract on days 5 and 12 respectively. In this test the 300 mg/kg dose of the extract showed a decline of 34.4 on day 5 and 56.4% on day 12. In addition, changes in body weight, serum lipid profiles, thiobarbituric acid reactive substance levels, glycosylated haemoglobin and liver glycogen levels assessed in the extract treated diabetic rats were compared with the diabetic control and normal animals. Significant results were observed in the estimated parameters, thereby justifying the use of the bijasar heartwood by Indian herbal practitioners for the treatment of diabetics in different parts of the country. Acknowledgements: CDACR, Bhopal for financial assistance.